Internal audit in the detection and prevention of errors and frauds: an analysis of companies in the industrial sector of Maracanaú – CE - Agostinho Mendes, Ana Nogueira (2022)
This paper aims at addressing the subject internal auditing as an aid in detecting and preventing errors and fraud, promoting a field study in companies in the industrial sector, steel manufacturers and distributors in the city of Maracanaú – CE. The study was conducted using information collected by the semi-structured interview technique applied to auditors and managers of companies from January 2019 to May 2021. The methodology used consisted of conducting an exploratory research with a qualitative approach. The results show that companies are adhering to the implementation of internal controls and considering internal auditing as an important tool in in detecting and preventing frauds and errors.